Migracje wewnętrzne i zagraniczne w aglomeracji poznańskiej w latach 1990-2011 - Walaszek , Marzena (Człowiek i Społeczeństwo, 2014)
Metropolitan areas in Poland are places of intense social, economic and spatial growth. The socioeconomic development of metropolitan areas is closely linked with the collective needs of the local society. These needs change over time and depend on the spatial scale of population movements, changes in the demographic structure and lifestyle. In the article, directions and reasons for migrations into the Poznań agglomeration in 1990-2011 were examined. The conclusion is that intensive development of housing affected the move to suburban areas.